Elemental Abundance Analyses With DAO Spectrograms - XXV. The Superficially Normal B and A Stars Alpha Ddraconis, Tau Herculis, Gamma Lyrae, and HR 7926 - Adelman, Saul J.; Çalışkan, H.; Koçer, Dursun; Kablan, H.; Yüce, K.; Engin, S. (My University, 2001)
Elemental abundances analyses of the superfically normal B and A stars alpha Dra (A0 III), tau Her (B5 IV), gamma Lyr (B9 III), and HR 7926 (B8 II-III) are performed consistent with previous studies of this series using spectrograms obtained with Reticon and CCD detectors. Comparisons of the first two analyses with those of the same stars performed earlier in this series which used mostly coadded photographic plates show the general consistency of the derived elemental abundances. A slight increase in the adopted effective temperature produces a corresponding increase in the derived abundances. In these stars the He/H ratios are found to be close to solar. Except for Lyr the metals show for the most part marginally subsolar abundance values. But this star has Al, Ca, Sc, and Sr abundances that are substantially underabundant as well as other underabundant values.
Keywords: Transition-Probabilites; Main-Sequence; Term System; F-Star; Spestrum; Compilation; Lifetimes; Titanium; Profile; Lines